Redundant Information? Repetitive Inscriptions in the Public Space of Pompeii - Fanny Opdenhoff (Cahiers des Études Anciennes)
Abstract : Inscriptions were very present in the public space of Pompeii. They were presented in different shapes and sizes along the streets, on building facades or at the forum square. Their content varies from honorary decrees, funerary inscriptions, the announcement of spectacles to personal notes or greetings. They were displayed so that every inhabitant or visitor could see, read or react on them. Many of the painted dipinti, the scratched graffiti and some of the stone inscriptions though, consist of identical or very similar texts that were then to be seen and read in different places all over the town. In three case studies about inscriptions from the building of Eumachia, the stelae of Titus Suedius Clemens and repetitive electoral programmata, different strategies can be observed in dealing with the placement and design of inscriptions. As the text remains unchanged, other factors like the layout, size and exact placement come to the foreground and show how the movement and expectations of the readers were taken into account.Résumé : Les inscriptions étaient très présentes dans l’espace public de Pompéi. Elles étaient présentées sous différentes formes et tailles le long des rues, sur les façades des bâtiments ou sur la place du forum. Leur contenu varie de décrets honorifiques, d’inscriptions funéraires, de l’annonce de spectacles à des notes personnelles ou des salutations. Elles étaient exposées de manière à ce que chaque habitant ou visiteur puisse les voir, les lire ou y réagir. Beaucoup de dipinti peints, de graffitis grattés et d’inscriptions sur pierre consistent cependant en des textes identiques ou très similaires qui pouvaient être vus et lus à différents endroits de la ville. Dans trois études de cas, sur les inscriptions du bâtiment d’Eumachia, la stèle de Titus Suedius Clemens et les programmata électoraux répétitifs, on peut observer différentes stratégies dans le traitement de l’emplacement et de la conception des inscriptions. Comme le texte reste inchangé, d’autres facteurs comme la disposition, la taille et l’emplacement exact passent au premier plan et montrent comment le mouvement et les attentes des lecteurs ont été pris en compte.